Participatory mapping and sustainability evaluation using the main agroecology structure: A study of cocoa and livestock agroecosystems in Caquetá Colombia - Clavijo, Neidy Lorena; Rodríguez, Luz Ángela; Álvarez, Javier Eduardo; Buitrago, Juliana; Gómez, Thomas (2024)
In Colombia's Caquetá department, analyzing the social and environmental aspects of cocoa and livestock farming is crucial for designing sustainable food systems that promote peace, climate resilience, and reduced emissions. The Main Agroecological Structure (MAS) method evaluates the design, connectivity, and management of these farms, considering both ecological and social factors. This allows for the development of strategies that mitigate climate change while improving livelihoods. Our findings suggest cocoa farms are more diverse and both systems have existing strengths in social aspects, indicating potential for transitioning towards more sustainable practices while considering farmer knowledge and environmental awareness.